2016
DOI: 10.1111/joim.12576
|View full text |Cite
|
Sign up to set email alerts
|

Randomized assessment of imatinib in patients with acute ischaemic stroke treated with intravenous thrombolysis

Abstract: Background Imatinib, a tyrosine kinase inhibitor, has been shown to restore blood–brain barrier integrity and reduce infarct size, haemorrhagic transformation and cerebral oedema in stroke models treated with tissue plasminogen activator. We evaluated the safety of imatinib, based on clinical and neuroradiological data, and its potential influence on neurological and functional outcomes. Methods A Phase II randomised trial was performed in patients with acute ischaemic stroke treated with intravenous thrombo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
40
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(42 citation statements)
references
References 37 publications
2
40
0
Order By: Relevance
“…10 Furthermore, animal studies and a pilot clinical study indicate that drugs that maintain the integrity of BBB may improve clinical outcome after acute ischemic stroke in tPA treated patients. 18,34,35 In our study, CED was associated with all types of SICH. Our data do not allow conclusions about the risk of CED in IVT patients versus non-IVT patients.…”
supporting
confidence: 57%
See 1 more Smart Citation
“…10 Furthermore, animal studies and a pilot clinical study indicate that drugs that maintain the integrity of BBB may improve clinical outcome after acute ischemic stroke in tPA treated patients. 18,34,35 In our study, CED was associated with all types of SICH. Our data do not allow conclusions about the risk of CED in IVT patients versus non-IVT patients.…”
supporting
confidence: 57%
“…The main outcome measurement, presence of edema classified in three types, has been used previously in the ECASS-2 and ECASS-3 trials (although not mentioned in the final publication) 16,17 , in a phase II clinical trial of imatinib 18 and in an analysis of local data from…”
Section: Discussionmentioning
confidence: 99%
“…Directly after acute ischemic stroke, tissue plasminogen activator (tPA) is used for thrombolysis, but beyond a few hours-long time window of therapeutic opportunity, tPA treatment is associated with intracerebral hemorrhage, a consequence of induced BBB breakdown. Along similar lines, the tyrosine kinase inhibitor imatinib, an efficient inhibitor of PDGFR signaling, was reported to reduce neurological disability after ischemic stroke [176]. The mechanism of PRGFRaÀinduced BBB disruption is not understood, but intriguingly, the expression of Pdgfra is largely restricted to perivascular fibroblasts among the different cell types of the NVU [17].…”
Section: Toward Therapy Developmentmentioning
confidence: 98%
“…The mechanism of PRGFRaÀinduced BBB disruption is not understood, but intriguingly, the expression of Pdgfra is largely restricted to perivascular fibroblasts among the different cell types of the NVU [17]. Along similar lines, the tyrosine kinase inhibitor imatinib, an efficient inhibitor of PDGFR signaling, was reported to reduce neurological disability after ischemic stroke [176]. As discussed above, pericytes are important for the constriction of capillaries and reduced CBF observed in the post-stroke situation [39,40].…”
Section: Toward Therapy Developmentmentioning
confidence: 99%
“…It was further demonstrated that the protein tyrosine kinase inhibitor, imatinib ('Gleevec'), that works downstream of the PDGF-CC activated PDGFRa1 receptor in perivascular astrocytes, inhibited the ability of t-PA to open the BBB [66]. This striking finding has recently led to clinical trials testing the effectiveness of imatinib in patients with ischaemic stroke, with positive preliminary findings [67].…”
Section: Fibrinolysis and The Brainmentioning
confidence: 99%